2010
DOI: 10.1002/tal.661
|View full text |Cite
|
Sign up to set email alerts
|

Design and behaviour of a reinforced concrete high‐rise tube building with belt walls

Abstract: SUMMARYThis paper discusses modelling, analysis and design issues for a 55‐storey hotel building recently planned for New York City, USA. The lateral force resistance of the investigated building primarily makes use of exterior reinforced concrete shear walls in one direction and exterior reinforced concrete moment frames in the other direction, in which tube action credited to the connection of the walls and frames was designed to play a significant role in the lateral stiffness and strength. In addition, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Depending on the responses of all modes, the use of HPFRCCs for some of the upper stories of walls or the reduction of reinforcement quantity in the lower stories of walls may need to be considered. 4. The HPFRCC coupling beams used in TB-2 showed more ductile behavior than normal concrete coupling beams in TB-1.…”
Section: Figure 45mentioning
confidence: 89%
See 1 more Smart Citation
“…Depending on the responses of all modes, the use of HPFRCCs for some of the upper stories of walls or the reduction of reinforcement quantity in the lower stories of walls may need to be considered. 4. The HPFRCC coupling beams used in TB-2 showed more ductile behavior than normal concrete coupling beams in TB-1.…”
Section: Figure 45mentioning
confidence: 89%
“…Since their emergence, tall buildings have been symbols and landmarks of economic breakthrough for developing countries. In the last couple of decades, tall buildings have rapidly increased in number, and the buildings have greatly benefited from progress in structural engineering and construction technologies . It is expected that the need for tall buildings will continue into the future due to their green benefits such as high‐density land use and efficient functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] The ETABS software [26] has been successfully employed for the analysis and design of high-rise buildings. [13,14,16] In these previous studies, similar modeling techniques, such as the use of frames for beams and columns and shell elements for shear walls, were adopted. [13,14,16] Moreover, the pin-end boundary condition has been widely used to simulate the connection between the upper and lower modules [8,9] ; it has been proven capable of predicting the experimental results of modular steel-braced frames under earthquake loading scenarios with satisfactory accuracy.…”
Section: Validation Of Numerical Modelmentioning
confidence: 99%
“…In recent years, numerous experimental, [12] numerical, [13,14] and analytical [15] studies on high-rise buildings have been performed; however, only a few have considered modular high-rise buildings. Liu et al [16] proposed a structural design method for a prefabricated high-rise steel structure; however, the structure was primarily composed of a prefabricated modular floor system and steel columns, rather than steel-framed modules.…”
Section: Introductionmentioning
confidence: 99%
“…The refractory materials commonly used in tall buildings are heterogeneous multiphase materials, generally composed of inorganic aggregates, binder phases and additives; the internal principal crystalline phase has a higher melting point and a certain thermal insulation effect [11]. By analysing the microstructure of building refractories, the mechanical properties and damage mechanisms of the materials can be established to predict the macroscopic properties of the refractory materials [12]. Park et al [13] used different building refractories (Table 1) in the study and found that their mechanical properties differ greatly for the refractories with different chemical compositions.…”
Section: Mechanical Damage Simulation Of Building Refractoriesmentioning
confidence: 99%